The Representation of Human Inner Conflict in the Topeng Tarung Dance - Regitha Vidia Pramesti; Agus Budiman; Tatang Taryana (Universitas Pendidikan Indonesia, 2025)
This study aims to describe the background behind the creation of a dance work that represents the internal conflict of human beings, expressed through choreographic structure, makeup, costume, and musical accompaniment. The research adopts a qualitative paradigm with a descriptive method, using an ethnocoreological approach to analyze both the text and context of Tarung Mask Dance. Data collection methods include observation, interviews, and documentation studies, analyzed using triangulation techniques. The findings reveal that the Tarung Mask Dance is a dance creation rooted in Sundanese traditional patterns. The dance is inspired by the theme of